PEMILIHAN ALTERNATIF SUMBER AIR BAKU DI KABUPATEN KARO - Simanjuntak, Salomo; Saragi, Yetty Riris; Simanjuntak, Johan Oberlyn; Pasaribu, Humisar; Sianipar, Ricki A H (Jurnal Visi Eksakta, 2021)
Clean water is a primary need for humans in every country. The availability of clean water must be guaranteed in time, quantity and quality. The need for water for both domestic and non-domestic needs continues to increase from year to year. To meet the needs of clean water, the people of Karo Regency need clean water sources that are suitable for drinking. Water resources are water discharge and population for water distribution. In finding the amount of water demand, an analysis of the population and analysis of clean water production is carried out. Determining the need for clean water and the population in Karo Regency uses the Geometry method which this method shows the largest population growth so that it can be planned for clean water needs until 2027. Based on the results of the projected population plus the number of water needs in 2027 as many as 491,444 people, the required water discharge is 907,799 l/s while the current production capacity is 14,744.831 l/s, so the additional capacity needed is 0.01003 m3/s. Implementation in the construction of clean water facilities must be adjusted to the level of social, cultural, and economic conditions of the community.